2011
DOI: 10.1103/physreva.84.042302
|View full text |Cite
|
Sign up to set email alerts
|

Quantum entanglement and quantum phase transition in theXYmodel with staggered Dzyaloshinskii-Moriya interaction

Abstract: We study the quantum entanglement and quantum phase transition (QPT) of the anisotropic spin-1/2 XY model with staggered Dzyaloshinskii-Moriya (DM) interaction by means of quantum renormalization group method. The scaling of coupling constants and the critical points of the system are obtained. It is found that when the number of renormalization group iterations tends to infinity, the system exhibit a QPT between the spin-fluid and Néel phases which corresponds with two saturated values of the concurrence for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 45 publications
(37 reference statements)
2
33
0
Order By: Relevance
“…The relevant investigation has estab- 10 lished deep links between quantum information theory and condensed matter physics. Recently, much attention has been focused on the role played by QD in QPT [14,15,16,17,18,19,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant investigation has estab- 10 lished deep links between quantum information theory and condensed matter physics. Recently, much attention has been focused on the role played by QD in QPT [14,15,16,17,18,19,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…An important applications of entanglement is to depict quantum phase transition (QPT) [5, 6,7,8,9,10,11,12,13]. The relevant investigation has estab- 10 lished deep links between quantum information theory and condensed matter physics.…”
Section: Introductionmentioning
confidence: 99%
“…After dividing the spin chain into blocks, each contains three sites. In the standard bases {| ↑↑↑ , | ↑↑↓ , | ↑↓↑ , | ↑↓↓ , | ↓↑↑ , | ↓↑↓ , | ↓↓↑ , | ↓↓↓ }, the block Hamiltonian of the three sites has two degenerate ground states [37]:…”
Section: Quantum Renormalization Of the Xy Model With Dzyaloshinskii-mentioning
confidence: 99%
“…It also has been shown that implementation of QRG method is helpful for detecting the nonanalytic and the scaling phenomenon in the vicinity of quantum critical points. [32][33][34][35][36][37]. Furthermore, since the above quantum correlation measures are available as new information-theoretical tools for quantum computation, it is very significant and indispensable for us to search for a quantum correlation measure as the universal indicator of quantum phase transition in the specific physical systems.…”
mentioning
confidence: 99%
“…Invoking such a method, surveys regarding Ising and Heisenberg models have been carried out in several works [22][23][24][25][26][27] and it has been shown that implementation of the QRG method is valuable in detecting the nonanalytic behavior of entanglement (concurrence) and the scaling behavior in the vicinity of CPs. Nevertheless, as mentioned above, entanglement is not sufficient to account for all the correlation contained in quantum systems, so this motivates us to apply other correlation witnesses to study their dynamic behaviors combining with QRG method.…”
Section: Introductionmentioning
confidence: 99%